KERAJINAN TENUN SONGKET WARNA ALAM NAGARI LINTAU BUO UTARA KABUPATEN TANAH DATAR - Nofi Rahmanita; Yuniarti Munaf (Institut Seni Indonesia Yogyakarta, 2021)
This paper is a study of natural color songket weaving craft in Lintau Buo Utara, West Sumatra. The research using qualitative methods with descriptive data and multidisciplinary approach. The results of this study explain that the Lintau Buo Utara songket weaving craft, which was born in 1996, uses natural dyes as a coloring agent for the songket threads. The use of natural dyes is an effort to reduce environmental pollution due to the use of synthetic dyes. The songket weaving decorations applied by the songket craftsmen of Nagari Lintau Buo Utara are sourced from traditional Minangkabau decorations and decorations created by the songket craftsmen themselves. Products made such as songket sarongs, scarves, and other derivative products. In the future, natural color songket weaving crafts will continue to exist and develop both in terms of the color of the songket weaving and the products produced. Makalah ini merupakan sebuah kajian kerajinan tenun songket warna alam di Lintau Buo Utara, Sumatera Barat. Penelitian dilakukan menggunakan metode kualitatif dengan data deskriptif dan metode pendekatan multidisplin. Hasil kajian ini menjelaskan bahwa kerajinan tenun songket Lintau Buo Utara yang lahir sejak tahun 1996, kain tenun songket yang dihasilkan memakai pewarna alam sebagai zat pewarna untuk benang songketnya. Pewarna alami digunakan untuk mengurangi pencemaran lingkungan yang disebabkan oleh pewarna sintetis. Ragam hias tenun songket yang diterapkan oleh perajin tenun songket Nagari Lintau Buo Utara bersumber dari ragam hias tradisonal Minangkabau dan ragam hias yang diciptakan oleh perajin songket itu sendiri. Produk yang dibuat, seperti sarung, selendang songket, dan produk turunan lainnya. Kerajinan tenun songket warna alam nantinya akan terus hadir dan berkembang baik dari segi warna kain tenun songketnya maupun produk yang dihasilkan.